(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Tuberculosis can entail any component of the gastrointestinaltract and is the sixth most common site of extra pulmonaryassociation. Both the incidence and severity ofabdominal tuberculosis are predictable to amplify withgrowingnumbers of HIV infection. Peritoneal tuberculosis, a type of abdominal tuberculosis, occurs in three forms: wet typewith ascites, dry type with adhesions, and fibrotic type withomental thickening and loculated ascites. Clinically, peritoneal tuberculosis ischaracterized by fever, abdominal pain, anorexia, weightloss, and ascites. Nevertheless, not any of these symptoms is accuratefor the disease, so it is frequently misdiagnosed, especiallyas carcinomatous peritonitis in the elderly. Diagnosisnear the beginning of peritoneal tuberculosis is of keyimpact in the control of thedisease. Chest X-rays demonstratesupport of associated pulmonarylesions in less than 25% of cases. Laparoscopywith direct biopsy is an exceptionalinvestigativetechniqueand should be considered for each patient with unsolvedascites. A classicconclusion requires detection ofbacilli in ascitic fluid or peritoneum tissue. However, acidfaststaining is frequently negative and cultures are positivein 30-40% of cases, making bacteriological evidence ofthe disease extremely difficult. In recent times, advances in moleculartechniques have provided aninnovative approach to the fast diagnosisof tuberculosis by nucleic acid probes and polymerasechain reaction. But if molecular techniques fail or unavailable, then presence of caseating granuloma in biopsy material is accepted as hallmark of extra-pulmonary tuberculosis and as significant as positive Acid Fast Bacillus (AFB) in pulmonary tuberculosis. Management is with conventionalanti-tubercular treatment for at least six months. J Shaheed Suhrawardy Med Coll, December 2016, Vol.8(2); 63-68